The Role of Traditional Leadership in Addressing Gender-Based Violence in Seke Community, Zimbabwe - Blessing Hodzi (African Journal of Inter-Multidisciplinary Studies)
This study examines the role of traditional leadership (village head and chiefs) in curbing gender-based violence (GBV) in rural communities. GBV disproportionately affects women in rural areas. The paper argues that traditional leaders have a role in addressing GBV in rural communities and posits that given the limited presence of formal institutions in rural communities, traditional leaders actively address and prevent GBV in their localities. This study is part of a 2022 Doctor of Philosophy thesis that explores the role of communal institutions in addressing GBV in Seke District, Ward 8, Zimbabwe. This study relies on qualitative research based on in-depth interviews and observations at the Chief's court. Findings from interviews with two officers and 10 village heads and chiefs and five observations that involved 14 participants indicate that traditional leaders use mediation, the traditional court system, referrals to the police, and awareness campaigns to address GBV. The study also indicates that food insecurity, infidelity, drug abuse, land ownership, and patriarchy are some of the drivers of GBV in the community. The paper recommends that the government, law enforcement, and private stakeholders use education on GBV to empower traditional leaders, who are essential players in addressing GBV in rural communities.